Diagnostic Challenges And Clinical Implications For Systemic EBV-Associated T-Cell Lymphoproliferative Disorders Of Childhood. (28th October 2020) - Yasa Benkli, C; Marcogliese, A; Elghetany, M; Punia, J; Fisher, K; Curry, C; El-Mallawany, N; Allen, C; McClain, K; John, T; Gaikwad, A
Abstract: Introduction/Objective: Systemic EBV-associated T-cell lymphoproliferative disorders of childhood (S-EBV-T-LPD) comprise three major forms: EBV-positive hemophagocytic lymphohistiocytosis (EBV-HLH), systemic EBV-positive T- cell lymphoma (S-EBV-TCL), and systemic T-cell chronic active EBV infection (S-T-CAEBV). These disorders are rare in children and young adults in Western countries and are associated with poor outcomes. Frequently patients were treated initially for EBV-HLH and subsequently found to have relapsed/refractory EBV-HLH vs S-EBV-TCL or overt EBV+ TCL, the latter of which requires different therapy than EBV-HLH. We report the clinicopathologic findings of 13 cases, including 8 previously reported. (PMID: 31099136) Methods: Thirteen cases of S-EBV-T-LPD were identified at Texas Children's Hospital from 1990 to 2020. Clinicopathologic and relevant laboratory parameters were recorded. Results: Patients included six females and seven males of Hispanic (n=6), Asian (4), and Caucasian origins (3) ages 1-22 years (median 2). All had fever, hepatosplenomegaly, cytopenias, abnormal EBV serologies, and significantly elevated peripheral blood EBV- DNA load by quantitative PCR. Histologic features were variable ranging from EBV+ T-cell infiltrates with subtle architectural distortion and mild atypia to overt morphologic appearance of lymphoma. Consistent findings were aberrant T-cell populations identified by immunohistochemistry (n=4) or bone marrow flow cytometry (n=9, 1-50%, mean 16%). Five patients were classified as overt EBV+ TCL with abnormal karyotyping identified in 3. Seven patients had pathology findings indistinguishable between EBV-HLH and S-EBV-TCL and were classified as EBV-HLH/S-EBV-TCL. One patient had S-T-CAEBV. Outcomes were dismal after HLH-directed immuno/chemotherapy protocols with/without bone marrow transplant as only three EBV-HLH/S-EBV-TCL patients were alive at 1.5, 2.5 months, and 9 years follow-up. Conclusion: This series from North America demonstrate challenges in the diagnosis and management of S-EBV-T- LPD cases. Particularly, EBV-HLH and S-EBV-TCL, which require vastly different treatment strategies, may initially present with overlapping clinicopathological features. Further studies are needed to address clear diagnostic criteria to guide appropriate management.